2010
DOI: 10.1167/10.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Face inversion impairs holistic perception: Evidence from gaze-contingent stimulation

Abstract: Human observers are experts at face recognition, yet a simple 180 degrees rotation of a face photograph decreases recognition performance substantially. A full understanding of this phenomenon-which is believed to be important for clarifying the nature of our expertise in face recognition-is still waiting. According to a long-standing and influential hypothesis, an inverted face cannot be perceived as holistically as an upright face and has to be analyzed local feature by local feature. Here, we tested this ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 84 publications
4
93
0
Order By: Relevance
“…This further demonstrated that P1 is related to the negativity bias [12,33,34], which is represented by individuals showing comparatively faster behavior speeds or greater ERP responses to negative stimuli than positive or neutral stimuli [36][37][38]. Besides, participants showed greater P1 amplitudes for inverted faces compared to upright faces, which is in line with face inversion effects that show it requires a longer response time and more cognitive and neural resources to identify inverted faces than upright faces [10,13,[39][40][41].…”
Section: Discussionsupporting
confidence: 64%
“…This further demonstrated that P1 is related to the negativity bias [12,33,34], which is represented by individuals showing comparatively faster behavior speeds or greater ERP responses to negative stimuli than positive or neutral stimuli [36][37][38]. Besides, participants showed greater P1 amplitudes for inverted faces compared to upright faces, which is in line with face inversion effects that show it requires a longer response time and more cognitive and neural resources to identify inverted faces than upright faces [10,13,[39][40][41].…”
Section: Discussionsupporting
confidence: 64%
“…Researchers have long known that turning a face upside down makes it harder to recognize [Yin 1969;Valentine 1988], and findings suggest that inversion affects the perception of face configuration more than the perception of local features [Van Belle et al 2010]. The part-whole method demonstrated that subjects are better at identifying face parts in the context of a whole face than in isolation [Tanaka and Farah 1993].…”
Section: Multimedia Processingmentioning
confidence: 99%
“…Its measures include the large reduction in face memory or discrimination for upside-down faces compared to upright faces (the "inversion effect"; Yin, 1969), the part -whole effect (which occurs for upright but not inverted faces; Tanaka & Farah, 1993), and the gaze-contingent window effect (again present upright but not inverted; Van Belle, de Graef, Verfaillie, Rossion, & Lefèvre, 2010). The most common measure, which we use here with S.P., is the composite effect (Young, Hellawell, & Hay, 1987): In this illusion, the appearance of the top half of one person's face alters when it is aligned with the bottom half of a different person (see Figure 1A), and the composite effect is measured as the disadvantage at identifying the top half in this aligned condition compared to a misaligned baseline.…”
Section: Holistic Processing In Dpmentioning
confidence: 99%